Prevalence and associated characteristics of anti-SARS-CoV-2 antibodies in Mexico-Dataset - González González, José Gerardo
This document contains the dataset on which conclusions of the manuscript "Prevalence and associated characteristics of anti-SARS-CoV-2 antibodies in Mexico 5 months after pandemic arrival" rely.